2011
DOI: 10.2485/jhtb.20.107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Analyses of Low-mineral-diet Ovariectomised Rat Femora Using Microscopic Computed Tomography

Abstract: The aim of this study was to monitor changes in bone density and bone quality (microarchitecture) in the femoral epiphyseal region in rats with bone loss induced by oestrogen deficiency and accelerated by mineral deficiency. Forty-eight Wistar rats were divided into 3 groups (n = 16 per group): Group 1, sham-operated rats on a normal diet; Group 2, ovariectomised rats on a normal diet; and Group 3, ovariectomised rats on a mineraldeficient diet. Observations were conducted 4, 8, 16, and 24 weeks after the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Since our present study indicates that osteoclast activity became more dominant than that of osteoblasts, the microstructures on the interior of the cortical bone must have been resorbed. Similar resorption was observed for cancellous bone trabeculae 12) . In the femur, which is a long bone, bone turnover is fast because of fast blood flow in the marrow cavity 25) , suggesting that trabecular resorption was enhanced.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Since our present study indicates that osteoclast activity became more dominant than that of osteoblasts, the microstructures on the interior of the cortical bone must have been resorbed. Similar resorption was observed for cancellous bone trabeculae 12) . In the femur, which is a long bone, bone turnover is fast because of fast blood flow in the marrow cavity 25) , suggesting that trabecular resorption was enhanced.…”
Section: Discussionsupporting
confidence: 66%
“…10). Moreover, since the blood mineral level was reduced in Group 3 because of reduced estrogen secretion and ingestion of a low-mineral diet, homeostasis might have been maintained by trabecular bone resorption 12) resulting in the lower bone density compared with that for Group 2 ( It has been reported that both bone formation and resorption are transiently promoted, and bone metabolic turnover was enhanced after OVX, and bone metabolism more rapidly responded in cancellous bone present in the marrow cavity than in cortical bone in long bones because of fast blood flow 25) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations